Analysis of Organizational Capacity of Public Schools in Adopting Educational Technology Innovation (Study at SDN 2 Hikun as a Google Reference School) - Muhammad Munawar Aulia Hamdi; Irawanto Tukiyat; Akhmad Abdurahman (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2026)
This study analyzes the capability of educators in implementing the Google Reference School Program at SDN 2 Hikun, Tabalong Regency, appointed through Letter Number B-233/DIKBUD/000.1.2.3/IV/2024. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving the principal, teachers, and parents as informants. The findings reveal two key dimensions: Pedagogical Competence falls in the Poor category, as most teachers still rely on conventional teaching methods with minimal use of Google Workspace for Education; while Professional Competence falls in the Fair category, as administrative requirements have been met and teachers understand the Google for Education ecosystem. Three main obstacles identified are inadequate infrastructure, limited digital literacy, and suboptimal platform utilization. Solutions include structured Google Certified Educator certification, infrastructure improvement, and stakeholder socialization